2017
DOI: 10.1073/pnas.1706206114
|View full text |Cite
|
Sign up to set email alerts
|

Early rearing history influences oxytocin receptor epigenetic regulation in rhesus macaques

Abstract: SignificanceEpigenetically programmed stress adaptation may be a conduit for informing offspring of environmental challenge. We employed ChIP-sequencing to examine effects of early environment on epigenetic regulation using hippocampal samples from macaques exposed to disruption in maternal care. We found decreased H3K4me3 binding at genes critical to behavioral stress response, the most robust being the oxytocin receptor gene (OXTR), for which we observed a corresponding decrease in RNA expression. Post hoc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 61 publications
2
35
1
2
Order By: Relevance
“…Oxytocin‐expressing neurons include a wide variety of cell types, such as GABAergic interneurons, glutamatergic pyramidal cells, and other peptidergic cells 34,37,38 . Oxytocin integrates brain and periphery, incorporates massive epigenetic inputs, and is particularly related to attachment experiences 39,40 . It increases plasticity in the hippocampal network to increase salience of the attachment target 41 , and attachment experiences shape oxytocin receptors availability 42 .…”
Section: Core Components Of the Neurobiology Of Affiliationmentioning
confidence: 99%
“…Oxytocin‐expressing neurons include a wide variety of cell types, such as GABAergic interneurons, glutamatergic pyramidal cells, and other peptidergic cells 34,37,38 . Oxytocin integrates brain and periphery, incorporates massive epigenetic inputs, and is particularly related to attachment experiences 39,40 . It increases plasticity in the hippocampal network to increase salience of the attachment target 41 , and attachment experiences shape oxytocin receptors availability 42 .…”
Section: Core Components Of the Neurobiology Of Affiliationmentioning
confidence: 99%
“…116 On the other hand, deprivation of early maternal care in rhesus macaques has been reported to suppress expression of the oxytocin receptor in the hippocampus via epigenetic regulation and induce higher separation anxiety, which was rescued by a certain oxytocin receptor gene single nucleotide polymorphism (SNP). 117 Neonatal maternal separation has also been shown to induce larger responses to noxious stimuli in an oxytocinand histone deacetylase-dependent manner in rats. 118 All of these reported findings suggest that expression of the oxytocin receptor is influenced by early experiences and modulates stress responsiveness in adulthood.…”
Section: Influence Of Early-life Experiences On Stress Responsesmentioning
confidence: 99%
“…Maternal care, or lack thereof, also seems to impact the expression of OXTR in rhesus monkeys. Indeed, peer-reared infants, compared to their mother-reared counterparts, showed altered epigenetic regulation of the OXTR gene (resulting in decreased OXTR mRNA in the hippocampus), and higher levels of separation anxiety and arousal (Baker et al, 2017). Subsequently it was shown that a naturally occurring gain-of-function nonsynonymous OXTR polymorphism partially rescued these behavioral differences.…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%